Engagement behavior on Facebook and the relationship between managers and consumers: the case of Icelandair - Arna Dögg Sigfúsdóttir 1991- (2019)
The intention of this study was to investigate consumer engagement behavior and consumer engagement on the Facebook page of Icelandair, an international airline operating from Iceland. Three separate studies were conducted. The first study went over Icelandair’s Facebook posts for the year 2018 (158 posts). The study measured which posts types received the most engagement, in terms of likes, reactions, comments and shares by using a conceptual model by de Vries, Gensler and Leeflang (2012). The results indicated that social posts, pictures and the interaction call-to-action had a positive effect on engagement. Furthermore, promotional posts and the interactivity a question in posts had a negative effect on engagement. The second study investigated through interviews the engagement behavior of Icelandair’s consumers. This was done by asking consumers about their engagement behavior on social media and about Icelandair’s Facebook page and what type of content they want to see from Icelandair. The third study were interviews with Icelandair’s managers to investigate the relationship between Icelandair and their consumers by using the bilateral contingency model from The Theory of the Marketing Firm (TMF). The interviews were coded and the results from the interviews indicated that consumers have very little memory of their engagement behavior, unless it is to partake in a Facebook game. Consumers though stated that content that they relate to, pictures, Facebook games, informational and entertaining content is the type of content they engage mostly with. The content that consumers would most like to see from Icelandair are more photos of destinations and flight offers. From the interview with the managers it can be seen that Icelandair by TMF’s definition is a customer-oriented company that bases their marketing efforts and strategy on research and feedback from their consumers.